CONTINUITY OF GAME FORMS OF TRAINING IN CONDITIONS OF THE EDUCATIONAL COMPLEX " SCHOOL- PRE-SCHOOL INSTITUTION" - Yuliia Zlotnitska; Nataliia Zakharasevych (Vasyl Stefanyk Precarpathian National University, 2018)
On the article the problem of implemetation continuity of game forms of training on conditions of the educational complex "school od preschool istitution" od analyzed. The author emphasizes on the implemetation of continuity of game forms in educational activity on the trandition from preschool to school. Continuity questions of game forms of training between preschool and school on historical terma their formation and development are analyzed. Key words: educational activity, continuity, game form of education, didactic game.